The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1039/c6ra27653a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2/Ti3C2Tx hybrid nanocomposites and their tribological properties as base oil lubricant additives

Abstract: TiO2/Ti3C2Tx hybrid nanocomposites were successfully prepared by a liquid phase synthesis technology. The hybrid nanocomposites improve the tribological properties of base oil by mending the surface and formation a uniform tribofilm on the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 39 publications
3
45
0
Order By: Relevance
“…Nb 2 CT x can be synthesized by HF etching, like most other MXenes. [65] The Nb/C ratio, which can be effectively increased by adding an amine, as illustrated in Figure 2A,i sd ependento nt he number of Nb atoms etched by HF in the etching process. [66] In the MAX phases, the Nb atomsc onsist of Nb top (on the top of the MXenes heets)a nd Nb bottom (on the bottomo ft he MXenes heets) atoms, both of which bond with Al atoms.…”
Section: Lithium-ion Battery Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…Nb 2 CT x can be synthesized by HF etching, like most other MXenes. [65] The Nb/C ratio, which can be effectively increased by adding an amine, as illustrated in Figure 2A,i sd ependento nt he number of Nb atoms etched by HF in the etching process. [66] In the MAX phases, the Nb atomsc onsist of Nb top (on the top of the MXenes heets)a nd Nb bottom (on the bottomo ft he MXenes heets) atoms, both of which bond with Al atoms.…”
Section: Lithium-ion Battery Electrodementioning
confidence: 99%
“…Apart from the Ti 3 C 2 T x MXene, the Nb 4 C 3 MXene is also a worthy anode material for LIBs. Nb 2 CT x can be synthesized by HF etching, like most other MXenes . The Nb/C ratio, which can be effectively increased by adding an amine, as illustrated in Figure A, is dependent on the number of Nb atoms etched by HF in the etching process .…”
Section: Energy Storagementioning
confidence: 99%
“…In Figure 4a, the layered structure of Ti 3 C 2 T x powders is obviously shown after the etching effect of HF solution. In Figure 4b, after the hydrothermal oxidation, even though anatase TiO 2 particles exist on the Ti 3 C 2 T x powders, the layered structure of Ti 3 C 2 T x powders still remain, deriving from the titanium atoms on Ti 3 C 2 T x , acting as nucleating sites for the growth of anatase TiO 2 [27]. The HRSEM image of the circle area displays the anatase TiO 2 with a thickness of~30 nm and length of~200 nm, and it can be observed that the interfacial angle between the {001} and {101} facets of anatase TiO 2 is about 68.3 • [28].…”
Section: Compositions Experimental Conditionsmentioning
confidence: 99%
“…[30][31][32] The MXenes have already showed their significant applicability in biosensors, [33] electromagnetic wave absorption, [34] supercapacitors, [35,36] Li-ion batteries, [37,38] electronic devices, [39,40] gas sensors, [41] etc., because of their high conductivity, [42] hydrophilic surface, [43] and flexibility. [46] It is anticipated that the formed composite could provide the TiO 2 NPs with the highly conductive supporting platform and prevent the self-aggregation by themselves, [47,48] indicating their great potential as a promising NRR catalyst, although this was paid little attention before. [12,45] Meanwhile, since the marginal titanium atoms on the Ti 3 C 2 T x MXenes surface are thermodynamically metastable, which could act as nucleating sites to enable the generation of relatively stable TiO 2 , thereby a heterojunction structure of TiO 2 nanoparticles (NPs) distributed at the 2D Ti 3 C 2 T x nanosheets (TiO 2 /Ti 3 C 2 T x ) could be facilely formed.…”
mentioning
confidence: 99%